PENGARUH PRIMING DENGAN EKSTRAK TOMAT DAN LAMA PERENDAMAN DENGAN Pseudomonas fluorescens TERHADAP VIABILITAS BENIH TERUNG BORNEO Lu (Solanum melongena L.) - Maulidyanti E. Sari; Raihani Wahdah; Bambang Fredricus (Universitas Lambung Mangkurat, 2022)
The objectives of this study were : To determine the effect of interaction between tomato fruit extract concentration and seeds soaking time with Pseudomonas fluorescens on the viability of eggplant seeds; To determine the effect of each tomato extract concentration and seeds soaking time with Pseudomonas fluorescens on the viability of eggplant seeds; To determine the best combination of tomato fruit extract concentration and seeds soaking time with Pseudomonas fluorescens on the viability of eggplant seeds. This study used a Factorial Completely Randomized Design (CRD) with separate control. The first factor was the concentration of tomato extract (K) and the second factor was soaking time with Pseudomonas fluorescens suspension. Consisting of four levels of tomato extract concentration, three levels of soaking time with of Pseudomonas fluorescens suspension, and one control treatment ((4x3)+1) with three replications each, so that 39 experimental units were obtained. The variables that were observed included seed germination, simultaneous growth, seed growth rate, root length, plumula length, and normal germination dry weight. The results showed that the treatment and control had a very significant effect on the variables of seeds germination and seeds growth rate. The interaction between tomato fruit extract concentration and soaking time with Pseudomonas fluorescens suspension was found in the variable of eggplant seeds germination. The single factor of soaking time with of Pseudomonas fluorescens suspension was found to have an effect on variable seeds growth rate. The best combination on viability of seeds was found in the treatment with 5% tomato extract concentration and the duration of soaking the seeds in Pseudomonas fluorescens suspention for 1 hour.